Efficacy of BCMA CAR-T cell therapy and subsequent strategies in refractory and relapsed plasma cell leukemia: a retrospective cohort study - Guo, Yuelu; Ma, Lixia; Yang, Fan; Fu, Zhonghua; Li, Danyang; Liu, Rui; Cao, Miaomiao; Wei, Bian; Dou, Yimeng; Deng, Biping; Gan, Shilin; Chang, Alex H.; et al. (Frontiers in Immunology, 2026)
BackgroundPlasma cell leukemia (PCL) is a rare and aggressive hematological malignancy. The long-term prognosis of relapsed/refractory plasma cell leukemia (R/R PCL) remains poor, and few treatment options are available for patients with triple-refractory disease. Chimeric antigen receptor (CAR)-T cell therapy targeting the B-cell maturation antigen (BCMA) has shown promise, though its long-term efficacy and optimal subsequent strategies remain to be fully elucidated.MethodsThis retrospective study analyzed the efficacy and safety of BCMA CAR-T therapy in 12 patients with triple-class R/R PCL. Patients were stratified into consolidation (Group 1, allo-HSCT within 3 months post-CAR-T) and non-consolidation (Group 2, no allo-HSCT within 3 months post-CAR-T) groups, with survival outcomes compared between cohorts.ResultsThe overall response rate following BCMA-CAR-T cell therapy was 75% (9/12); four patients achieved partial response, four achieved very good partial response, and one patient had complete response. Grade 3–4 cytopenia were universally observed, while 83.3% (10/12)of the patients presented with mild (grade 1-2) cytokine release syndrome. The median progression free survival (PFS) was 8.9 months (95% CI: 4.6, not reached). The 1-year PFS rate was 33.3% (95% CI: 7.8–62.3), and the 2-year PFS rate was 22.2% (95% CI: 3.4–51.3). The median overall survival (OS) was 15.5 months (95% CI: 5.7, not reached). The 1-year OS rate was 55.6% (95% CI: 20.4–80.5), and the 2-year OS rate was 22.2% (95% CI: 3.4–51.3). furthermore, two of the four patients who underwent consolidation therapy showed long-term survival with stringent complete response.ConclusionsBCMA-CAR-T therapy confers short-term remission and survival benefits in relapsed/refractory plasma cell leukemia (R/R PCL). However, the definitive value of allogeneic hematopoietic stem cell transplantation (allo-HSCT) awaits validation in large-sample prospective studies.